2000
DOI: 10.1038/sj.ejhg.5200502
|View full text |Cite
|
Sign up to set email alerts
|

A new human genetic resource: a DNA bank established as part of the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC)

Abstract: We describe a unique human DNA resource forming part of the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC), a longitudinal cohort study involving 14 000 children and their families living in a geographically defined area of England. The DNA bank will underpin the search for associations between genetic polymorphisms and common health outcomes. The opportunities to collect blood samples suitable for DNA extraction are necessarily limited, and the samples themselves have often been treated in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 5 publications
0
69
0
Order By: Relevance
“…Our aim in this study is to further investigate the relationship between the genetic variants in BDNF and BMI by genotyping the same genetic variants in BDNF in two sizable and well-characterized populations of British women: (1) the British Women's Heart and Health Study (BWHHS); and (2) the mothers from the Avon Longitudinal Study of Parents and Children (ALSPAC). 10,11 Both studies have considerably greater statistical power than the original published study of this association, 9 and than a second published study that also reported a null association.…”
Section: Introductionmentioning
confidence: 88%
“…Our aim in this study is to further investigate the relationship between the genetic variants in BDNF and BMI by genotyping the same genetic variants in BDNF in two sizable and well-characterized populations of British women: (1) the British Women's Heart and Health Study (BWHHS); and (2) the mothers from the Avon Longitudinal Study of Parents and Children (ALSPAC). 10,11 Both studies have considerably greater statistical power than the original published study of this association, 9 and than a second published study that also reported a null association.…”
Section: Introductionmentioning
confidence: 88%
“…There were 14,062 liveborn children. The study protocol has been described previously 43,44 and further details are on the ALSPAC website:…”
Section: Study Populationsmentioning
confidence: 99%
“…One control series consisted of buccal scrape samples from children (n ¼ 64) and blood samples from their parents (n ¼ 128), recruited as part of the UK Childhood Cancer Study (2000) in the North West (NW) of England. The second control series consisted of blood samples from children (n ¼ 60) obtained as part of the Avon Longitudinal Study of Parents and Children (ALSPAC; Jones et al, 2000) and buccal samples from their parents (n ¼ 120; Ring et al, 2001). Sample collection and analyses were carried out with the approval of Local Research Ethics Committees.…”
Section: Case and Control Samplesmentioning
confidence: 99%